The Relationship between the Level of Nutritional Awareness and Healthy Nutritional Behavior of Women in Lattakia city- Syria - Dona, Issa Abboud (Latakia University Journal -Medical Sciences Series, 2020)
Researchers are increasingly interested in assessing the levels of nutritional awareness among children, adolescents and adults by studying the factors that cause obesity, identifying dietary dysfunction, and the dietary patterns followed by rapid developments in various aspects of economic, social and technological life. Find ways to reduce their spread as a serious disease that causes many chronic diseases that greatly increase the mortality rate. The aim of the study was to evaluate the level of nutritional awareness among women in Syria, to assess their nutritional behavior, to study the relationship between the level of nutritional awareness and nutritional behavior, and the impact of nutritional awareness on obesity indicators of women. To achieve this, four main hypotheses were formulated. The researcher used the questionnaire tool to collect the data, which was analyzed using statistical tests, the most important of which were: the one-sample T. test and the Pearson Correlation. The researcher found several results, the most important of which is: a low overall assessment of the level of women's nutritional awareness, and for their nutritional behavior, and a strong positive correlation between the level of nutritional awareness and nutritional behavior. تزايد اهتمام الباحثين بتقييم مستويات الوعي الغذائي لدى الأطفال والمراهقين والبالغين من خلال دراسة العوامل المسببة للسمنة، وتحديد الخلل في السلوك الغذائي، والأنماط الغذائية المتبعة والتي فرضتها التطورات المتسارعة في مختلف جوانب الحياة الاقتصادية والاجتماعية والتكنولوجية، وتزايدت معدلات انتشار السمنة العالمية بشكل ملحوظ، مما يبرر أهمية إيجاد السبل اللازمة للحد من انتشارها باعتبارها من الأمراض الخطيرة التي تسبب العديد من الأمراض المزمنة والتي تزيد من معدل الوفيات بشكل كبير. يهدف البحث إلى دراسة تقييم مستوى الوعي الغذائي لدى السيدات في سورية، وتقييم سلوكهن الغذائي، ودراسة العلاقة بين مستوى الوعي الغذائي والسلوك الغذائي، وتأثير الوعي الغذائي على مؤشرات السمنة لدى السيدات، ولتحقيق ذلك تمّ صياغة أربع فرضيات رئيسة، واستخدم الباحث أسلوب الاستبانة لجمع البيانات الّتي تمّ تحليلها باستخدام اختبارات إحصائيّة أهمّها: اختبار الوسط الحسابي One- Sample T. test، واختبار الارتباط الثّنائي Pearson Correlation. وقد توصل الباحث إلى عدّة نتائج أهمّها: وجود تقييم إجمالي ضعيف لمستوى الوعي الغذائي لدى لسيدات، ولسلوكهن الغذائي، ووجود علاقة طردية معنوية قوية بين مستوى الوعي الغذائي والسلوك الغذائي.